PS01.092: FOKER GROWTH INDUCTION FOR LONG GAP ESOPHAGEAL ATRESIA: WHAT WE HAVE LEARNED. (14th September 2018) - Jo Svetanoff, Wendy; Bairdain, Sigrid; Zurakowski, David; Hamilton, Thomas; Clark, Susannah; Ngo, Peter; Manfredi, Michael; Jennings, Russell; Gallagher, Dorothy; Smithers, C
Abstract: Background: The Foker process is used in patients with long-gap esophageal atresia (LGEA) to maintain the native esophagus; however, chemical paralysis, used to 'protect' the esophagus, is associated with complications and longer hospital stays. The purpose of this study was to identify changes in practice patterns with increased Foker experience, and to review the relationship of paralysis time with the incidence of esophageal leaks and need for stricture resections. Methods: A retrospective review of LGEA patients from January 2006 to December 2016 was performed. Patients were excluded if they had previous attempts elsewhere. Patients were initially divided into two groups: early group (surgery before 2013) and late group (2013–2016) to assess outcomes. All patients, irrespective of surgery date, were then divided into three subgroups based on esophageal anastomotic tension. Logistic regression with odds ratio (OR) and 95% confidence interval (CI) was used to assess risk of leaks and need for stricture resection. Results: Fifty-eight patients met criteria, and demographics were similar between groups. The late group required significantly fewer surgeries between Foker I and Foker II and had shorter ICU length of stay (LOS). Variables that trended towards statistical significance included total length of paralysis, time between Foker I and Foker II, and total hospital LOS. Overall, 18 patients developed a leak, and 13 required stricture resections. There was no correlation between paralysis time or anastomotic tension with incidence of leak or stricture resection. Multivariable analysis indicated that the occurrence of a leak (OR 5.7, 95% CI: 1.4–27.3, P  = 0.025) and need for > 8 dilations (OR 11.0, 95% CI: 2.3–53.4, P  = 0.002) were significant predictors of need for stricture resection. Conclusion: As our experience has grown, the need for multiple procedures between Foker I and Foker II has decreased, leading to less paralytic exposure, shorter ICU LOS, and trending toward decreased hospital LOS. By verifying that specified paralysis times are not required, we can continue to mitigate complications associated with lengthy paralysis times and longer hospital admissions without risking esophageal health. Disclosure: All authors have declared no conflicts of interest.